Alcohol use severity, depressive symptoms, and optimism among Hispanics: Examining the immigrant paradox in a serial mediation model. Issue 12 (27th June 2020) - Cobb, Cory L.; Schwartz, Seth J.; Salas‐Wright, Christopher P.; Pinedo, Miguel; Martinez, Priscilla; Meca, Alan; Isaza, Alejandra G.; Lorenzo‐Blanco, Elma I.; McClure, Heather; Marsiglia, Flavio F.; Martínez, Charles R.; Cano, Miguel Ángel
Abstract: Objective: Hispanic immigrants exhibit more positive outcomes than U.S.‐born Hispanics across educational, psychological, and physical health indices, a phenomenon called the immigrant paradox. We examined the immigrant paradox in relation to alcohol use severity among Hispanic young adults while considering both positive (optimism) and negative (depressive symptoms) processes. Method: Among 200 immigrant and U.S.‐born Hispanic young adults ( M age = 21.30; 49% male) in Arizona and Florida, we tested whether optimism and depressive symptoms statistically mediated the relationship between nativity and alcohol use severity. Specifically, we examined whether Hispanic immigrants reported greater optimism than their U.S.‐born counterparts, and whether such optimism was, in turn, associated with less depressive symptoms and thus lower alcohol use severity. Results: Indirect effects were significant in hypothesized directions (nativity → optimism → depressive symptoms → alcohol use severity). Conclusions: Both positive and negative psychological processes are important to consider when accounting for the immigrant paradox vis‐à‐vis alcohol use severity among Hispanic young adults.